2013
DOI: 10.1007/s00432-013-1504-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopy and laparotomy for management of endometrial carcinoma: a prospective randomized study with 11-year experience

Abstract: Laparoscopic surgery is a safe and reliable alternative to laparotomy in the management of endometrial carcinoma patients, with significantly reduced hospital stay and postoperative complications; however, it does not seem to improve the overall survival and 5-year survival rate, although multicenter randomized trials are required to evaluate the overall oncologic outcomes of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…Seven studies reported all safety outcomes, 3,15,17,18,20,21,24 conversion rates of TLH to TAH, and intraoperative and postoperative complications, and 2 reported information on postoperative complications only. 16,22 All patients had International Federation of Gynecology and Obstetrics (FIGO) stages I to IV endometrial cancer. For 3 studies, 16 The LACE 3 and LAP-2 4 studies were designed to establish NI of TLH and had prespecified NI margins of 7% at 4.5 years (LACE) and 5.3% at 3 years (LAP-2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies reported all safety outcomes, 3,15,17,18,20,21,24 conversion rates of TLH to TAH, and intraoperative and postoperative complications, and 2 reported information on postoperative complications only. 16,22 All patients had International Federation of Gynecology and Obstetrics (FIGO) stages I to IV endometrial cancer. For 3 studies, 16 The LACE 3 and LAP-2 4 studies were designed to establish NI of TLH and had prespecified NI margins of 7% at 4.5 years (LACE) and 5.3% at 3 years (LAP-2).…”
Section: Resultsmentioning
confidence: 99%
“…16,22 All patients had International Federation of Gynecology and Obstetrics (FIGO) stages I to IV endometrial cancer. For 3 studies, 16 The LACE 3 and LAP-2 4 studies were designed to establish NI of TLH and had prespecified NI margins of 7% at 4.5 years (LACE) and 5.3% at 3 years (LAP-2). For the LACE study, the NImargin at 3 years would be 4.9%, based on an exponential distribution and 3-year DFS rates of 93.2% (TAH) and 88.3% (TLH).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That fact is common in most of the studies published, 3,4,6,7,15 except of one. 13 It is also important to note that the development of the study coincided with the learning curve of the laparoscopic surgeons of our hospital, and this fact may have contributed to elongate the surgical procedure.…”
Section: Discussionmentioning
confidence: 90%
“…3,4,7 However, data related to recurrence rate and long-term survival are limited. 13 During laparoscopic approach, the upward traction to the uterus turns to be fundamental to achieve a successful procedure. That fact can be possible with the use of uterine manipulators in hysterectomy.…”
mentioning
confidence: 99%